LB01.05: VASCULAR CONSEQUENCES OF PRE-ECLAMPSIA. (June 2015) - Brown, C.E.; Flynn, J.; Carty, D.M.; Scotland, Generation; Delles, C.
Abstract : Objective: Women with a history of pre-eclampsia (PE) are at higher risk of cardiovascular disease later in life. We evaluated the cardiovascular health of women who had PE in comparison with women who had normotensive pregnancies. Design and method: Women were recruited from the previous Proteomics in Pre-eclampsia (PIP) Study, the Generation Scotland Scottish Family Health Study and the Glasgow Blood Pressure Clinic (pregnancies 1–5, 10–30 and 1–30 years ago, respectively). We assessed heart rate-adjusted augmentation index (AIx; SphygmoCor), carotid-femoral pulse wave velocity (PWV; SphygmoCor), carotid intima-media thickness (CIMT; ultrasound) and brachial flow-mediated dilatation (FMD; ultrasound). Results: A total of 166 women (86 cases, 80 controls) attended for vascular studies. Women with a history of PE had higher systolic blood pressure (SBP) (130 ± 14 vs 122 ± 10 mmHg; P < 0.001) and diastolic blood pressure (DBP) (82 ± 9 vs 78 ± 7 mmHg; P = 0.001) compared with controls. They also had a higher BMI (29.4 ± 6.1 vs 26.6 ± 4.5 kg/m 2 ; P = 0.002). We found impaired endothelial function (FMD 5.9 ± 3.3 vs 7.0 ± 3.3 %, P = 0.017) and greater PWV (7.8 ± 1.6 vs 7.1 ± 1.1 m/s, P = 0.002) and heart rate-adjusted AIx (25.7 ± 11.0 vs 22.5 ± 9.6 %, P = 0.023) in cases compared with controls. There was no difference in CIMT (P = 0.110). After adjustment for age, BMI and SBP the difference in endothelial function remained statistically significant (P = 0.014). Conclusions: Women who had PE have higher blood pressure and BMI compared to women at similar age who had normotensive pregnancies. A history of PE is also associated with impaired endothelial function which could explain the higher cardiovascular risk in this group.